'Do they not have rational souls?': consolidation and sovereignty in digital new worlds. (1st October 2016) - Byrd, Jodi A.
ABSTRACT: 'Prepare to die' ads for the video game series Dark Souls warn, and indeed the series is known for its punishing, hard core gameplay that promises gamers failure over and over again. Notorious and celebrated for its difficulty, the game series created by FromSoftware, Inc. presents players with an alienated world of violence that demands exploration tied to conquest to control space, advance past demonic creatures, and achieve dominance over terrain. Along the way, players collect the souls of defeated enemies and use them to acquire skills, weapons, and the tools necessary to survive. This article considers the rise of late colonialism alongside neoliberal consolidations of self, narrative, and expression within social, digital, and videogame conventions. Reading the Demon's Souls/Dark Souls series alongside Bartolomé de Las Casas' A Short Account of the Destruction of the Indies, Carl Schmitt's The Nomos of the Earth, and Tzvetan Todorov's Conquest of America, this article examines how structures of colonialism depend upon the procedural elements of enclosure, capture, and narrative to procedurally conscript the Americas into settler colonial territoriality.